2009
DOI: 10.1038/jid.2008.268
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Protein Psoriasin (S100A7) Is Upregulated in Atopic Dermatitis and after Experimental Skin Barrier Disruption

Abstract: The innate defense of the skin against microbial threats is influenced by antimicrobial proteins (AMP). Staphylococcus aureus often colonizes the skin of patients with atopic dermatitis (AD). This was explained by diminished expression of AMP including cathelicidin/LL-37, human beta-defensins-2 and -3, and dermcidin. The S100-protein psoriasin is an additional keratinocyte-derived AMP that preferentially kills E. coli. As E. coli infections are not observed in atopic skin we investigated the functional role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
3
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(166 citation statements)
references
References 78 publications
12
138
3
2
Order By: Relevance
“…Table 1. Filaggrin, loricrin, S100A7, and S100A8 expression in lesional skin of patch, plaque, tumor, erythroderma of CTCL, atopic dermatitis, psoriasis and in normal skin filaggrin loricrin S100A7 S100A8 Normal 5 0% 40% 60% 0% 40% 60% 80% 20% 0% 80% 20% 0% CTCL (patch) 5 20% 60% 20% 40% 60% 0% 60% 40% 0% 40% 60% 0% CTCL (plaque) 5 60% 40% 0% 60% 40% 0% 60% 40% 0% 60% 20% 20% CTCL (tumor) 5 80% 20% 0% 80% 20% 0% 60% 40% 0% 40% 60% 0% CTCL (erythroderma) 5 80% 20% 0% 60% 40% 0% 80% 20% 0% 60% 40% 0% Atopic dermatitis 5 80% 20% 0% 80% 20% 0% 40% 60% 0% 60% 40% 0% Psoriasis 5 80% 20% 0% 80% 20% 0% 0% 40% 60% 0% 40% (44)(45)(46). Consistently, in CTCL lesional skin, we detected significant negative correlations between expression levels of S100A7 and those of CCL26 or CCR3, a representative T H 2 chemokine/chemokine receptor pair (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1. Filaggrin, loricrin, S100A7, and S100A8 expression in lesional skin of patch, plaque, tumor, erythroderma of CTCL, atopic dermatitis, psoriasis and in normal skin filaggrin loricrin S100A7 S100A8 Normal 5 0% 40% 60% 0% 40% 60% 80% 20% 0% 80% 20% 0% CTCL (patch) 5 20% 60% 20% 40% 60% 0% 60% 40% 0% 40% 60% 0% CTCL (plaque) 5 60% 40% 0% 60% 40% 0% 60% 40% 0% 60% 20% 20% CTCL (tumor) 5 80% 20% 0% 80% 20% 0% 60% 40% 0% 40% 60% 0% CTCL (erythroderma) 5 80% 20% 0% 60% 40% 0% 80% 20% 0% 60% 40% 0% Atopic dermatitis 5 80% 20% 0% 80% 20% 0% 40% 60% 0% 60% 40% 0% Psoriasis 5 80% 20% 0% 80% 20% 0% 0% 40% 60% 0% 40% (44)(45)(46). Consistently, in CTCL lesional skin, we detected significant negative correlations between expression levels of S100A7 and those of CCL26 or CCR3, a representative T H 2 chemokine/chemokine receptor pair (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…К сожалению, некоторые из этих маркёров, такие как протеины S100 А7, А8 и А9, экспрессируются не только при псори-азе [25,33], но также в случае других воспали-тельных кожных заболеваний [16,29]. В работах M. Nold и соавт.…”
Section: современные представления об этиопатогенезе псориаза и псориunclassified
“…(2013) показана увеличенная экс-прессия IL-36γ в коже у пациентов с псориазом (n=38 и n=17) [20]. В отличие от других маркё-ров, описанных раннее при псориазе, например S100 А7, А8 и А9 [16,23,25,33], маркёр IL-36γ ока-зался высокоспецифичным для псориаза (при других воспалительных заболеваниях кожи, в том числе атопическом дерматите и контактной экземе, экспрессия выражена слабо) [20].…”
Section: роль Il-36γ в воспалительных заболеваниях кожиunclassified
“…Researches revealed a lower expression of hBD-2, hBD-3 and LL-37 in the skin of patients with AD when compared to psoriasis vulgaris [44,45]. A possible explanation could be the lack of major inducers in the AD skin, such as IL-1, IL-17 and IL-22, alongside with inhibition of AMPs induction by an elevated level of Th2 cytokines (IL-4, IL-10 and IL-13) [46]. However, the observation of AMPs in AD was based on the comparison to the lesional psoriatic skin, and not to healthy one.…”
Section: Clinical Relevance Of Amps In Inflammatory Skin Disordersmentioning
confidence: 99%
“…It was revealed that the expression of psoriasin, a strong E. coli killing AMP, in non-lesional and lesional skin of untreated patients with AD is increased in comparison to healthy controls [46]. Nevertheless, the role of AMPs in the pathogenesis of AD is still unclear.…”
Section: Clinical Relevance Of Amps In Inflammatory Skin Disordersmentioning
confidence: 99%